(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Emotion is a fundamental driver of consumer decision-making, influencing preferences, perceptions, and purchasing behaviors in profound ways. While rationality plays a role in choices, emotions often serve as the underlying force shaping how consumers interpret and interact with products, brands, and experiences. Emotional responses—such as joy, trust, or nostalgia—affect both conscious and subconscious decision-making processes, making them a key area of focus for marketers aiming to connect with audiences on a deeper level. Emotions enhance memory and brand recall, as experiences imbued with emotional significance are more vivid and enduring. This principle underpins the success of emotionally charged marketing campaigns that leverage storytelling, imagery, and relatable themes to create lasting impressions. Additionally, emotions influence perception, framing how consumers evaluate risks, benefits, and the overall value of offerings. For instance, positive emotions can heighten optimism and trust, whereas negative emotions may foster skepticism or avoidance. Impulse buying, brand loyalty, and online engagement further underscore emotion’s pervasive role. Immediate emotional gratifications drive spontaneous purchases, while enduring positive emotions foster deep connections and repeat business. Digital platforms amplify emotional influences through user-centered design and viral content, creating opportunities for brands to evoke engagement and trust.